From Free Flow to Structured Lines: Comparing Kindergarten Children’s Drawings - Prayitno Prayitno; Nurul Arifiyanti; Oktaviana Maharani; Rini Agustiningsih; Muhammad Ghufron Eka Saputra (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study examines the differences in drawing patterns of kindergarten children during free drawing and guided drawing, using educational video stimuli. The research aims to describe the characteristics of children’s drawings in both contexts and analyze changes that occur after receiving visual guidance. Employing a descriptive quantitative approach with a one-group pretest–posttest design, the study involved 25 children aged 5–6 years selected through purposive sampling. Data were collected using observation sheets that assessed eight indicators of early childhood drawing development, including clarity and detail of form, balance of size and layout, and purposeful use of color. Pretest activities consisted of a 20-minute free drawing session, followed by a posttest after participants watched a 5–7-minute educational video about bees. Descriptive analysis showed an increase in the overall mean score from 2.5 (pretest) to 3 (posttest), indicating notable improvement across all indicators. Children’s posttest drawings displayed clearer and more detailed bee forms, more balanced composition, and purposeful color application. These findings suggest that structured visual media effectively support children’s perceptual-motor and visual-spatial skills, and can be used as a practical strategy to enhance artistic and cognitive development in early childhood classrooms.